Weakness and collapse of bee colonies in Brazil: are there cases of CCD? - Soares Pires, Carmen Silvia; Pereira, Fabie de Mello; Rego Lopes, Maria Teresa do; Ferreira Nocelli, Roberta Cornelio; Malaspina, Osmar [UNESP]; Pettis, Jeffery Stuart; Teixeira, Erica Weinstein (Empresa Brasil Pesq Agropec, 2016)
In the last decades, the decline of wild bee populations and the collapse of Apis mellifera colonies have concerned researchers and beekeepers. The objective of this review was to compile some of the most relevant studies related to the possible causes of these problems such as nutrition, management, pathogens, parasites, and the effects of pesticides, besides presenting a brief history of the colony collapse disorder syndrome (CCD) in the United States and Europe. The studies developed in Brazil were presented in more detail, mainly those on pesticides used in agriculture and on pathogens and parasites that attack the colonies of Africanized A. mellifera. Cases of weakening, decline, and collapse have been recorded in Brazil, mainly in the states of Sao Paulo and Santa Catarina, which add up to great losses. Results of the analyzed occurrences indicated that the recorded mass mortalities were not associated with pathogens or parasites. Only two cases with characteristics similar to those described for CCD were recorded, but without defined causes. In order to know the causes of the weakening and collapses of colonies, the implementation of official programs is urgent for the systematic survey of bee health, associated with research focusing on assessments of possible impacts of habitat fragmentation and agricultural practices on bee communities.
Keywords: Apis mellifera; Africanized honey bees; colony collapse disorder; bee nutrition; honey bee health; pollination